Bruton's tyrosine kinase is a Toll/interleukin-1 receptor domain-binding protein that participates in nuclear factor kappaB activation by Toll-like receptor 4 - O'NEILL, LUKE ANTHONY JOHN (American Society for Biochemistry and Molecular Biology, 2003)
In this study we have identified members of the Toll-like receptor (TLR) family (namely, TLRs 4, 6, 8, and 9) as proteins to which the intracellular protein tyrosine kinase, Bruton's tyrosine kinase (Btk), binds. Detailed analysis of the interaction between Btk and TLR8 demonstrates that the presence of both Box 2 and 3 motifs in the Toll/interleukin-1 receptor domain was required for the interaction. Furthermore, co-immunoprecipitation experiments revealed that Btk can also interact with key proteins involved in TLR4 signal transduction, namely, MyD88, Mal (MyD88 adapter-like protein), and interleukin-1 receptor-associated kinase-1, but not TRAF-6. The ability of Btk to interact with TLR4 and Mal suggests a role for Btk in lipopolysaccharide (LPS) signal transduction. Stimulation of the human monocytic cell line THP-1 with LPS resulted in an increase in the level of tyrosine phosphorylation of Btk (indicative of activation). The autokinase activity of Btk was also stimulated after LPS stimulation. In addition, a dominant negative form of Btk inhibited TLR4-mediated activation of a nuclear factor kappaB (NFkappaB)-dependent reporter gene in HEK293 cells as well as LPS-induced activation of NFkappaB in the astrocytoma cell line U373 and the monocytic cell line RAW264.7. Further investigation revealed that the Btk-specific inhibitor, LFM-A13, inhibited the activation of NFkappaB by LPS in THP-1 cells. Our findings implicate Btk as a Toll/interleukin-1 receptor domain-binding protein that is important for NFkappaB activation by TLR4.
PUBLISHED
Keywords: Biochemistry